EFEK PENAMBAHAN LIMBAH BATUBARA PADA LEMPUNG PLASTISITAS TINGGI TERSTABILISASI SEMEN TERHADAP CBR - Satibi, Syawal; Nugroho, Soewignjo agus; Putra, agus ika; Zega, Christian Robert (Jurnal Jalan Jembatan, 2024)
High plasticity clay (CH) has poor material characteristics, such as considerable shrinkage due to high plasticity, so soil improvement is needed, for example, using cement and coal waste (bottom ash and fly ash, BAFA). The purpose of adding cement and BAFA type C is to see the effect on changes in soil CBR values. Variations in BAFA addition are 4%, 8%, 12% and 16% and PCC cement 3% and 5%. The percentage of bottom ash content to fly ash in BAFA is 2:1. Based on the test results, an increase in the CBR bearing capacity value was seen from 0.78% in the original soil to 18% in samples with a mixture of 5% cement and 16% BAFA with 7 days of curing. The CBR sample S5-B16-C7 is the largest value of all sample variations. The increase in the CBR value is huge from 0,78% to 18.73% This value proves that the combination of mixtures can effectively increase soil-bearing capacity. Based on microscopic testing of CBR samples, it can be seen that the higher the BAFA and Cement content, the rougher and paler the changes in the sample structure are. Conversely, the sample structure is smoother at the lowest BAFA content and cement content, and the sample colour is brighter, approaching the original soil colour. The results of this study indicate that BAFA can be used as pavement materials and provide a solution to the environmental impact of industrial waste.